(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
The present research was focused in drawing the pharmacopoeial monographs along with preliminary phytochemical analysis of Annona muricata Linn (leaf). Pharmacognostical studies and phytochemical analysis was carried out by using standard procedures. Pharmacognostical parameters such as macroscopy, microscopy, quantitative microscopy, powder analysis, behaviour of powder with various reagent. Phytochemical screening of the hydroalcoholic extract was performed to investigate the presence of secondary metabolites. Leaves of Annona muricata, simple entire margin, equal base acuminate apex, length - 6.48-12.68cm, breadth 2.08- 4.4cm, alternate phyllotaxy and reticulate venation. Transverse section of leaf showed upper epidermis with thin cuticle, followed by ground cells nad mid rib, that consists of vascular bundle, parenchymatous cells and collenchyma. Quantitative microscopy parameters such as vein islet number, vein termination number, stomatal number, stomatal index and epidermal cells. Powder microscopical analysis showed the presence of uniseriate multicellular covering trichomes, pitted vessels, bundle of fibres and calcium oxalate crystals. Behaviour of powder with various reagent characterised the colour change under visible light and UV of short and long wavelength. Preliminary Phytochemical screening detect the presence of flavonoids, alkaloids, tannin, reducing sugar and phenolic compounds. The results have established a clear identification, authentication pharmacognostical frame work for the leaves of Anona muricata. The results of this study reported that hydroalcoholic extract revealed the presence of alkaloids, flavonoids and phenols.